2013
DOI: 10.1371/journal.pone.0080886
|View full text |Cite
|
Sign up to set email alerts
|

High Theta and Low Alpha Powers May Be Indicative of BCI-Illiteracy in Motor Imagery

Abstract: In most brain computer interface (BCI) systems, some target users have significant difficulty in using BCI systems. Such target users are called ‘BCI-illiterate’. This phenomenon has been poorly investigated, and a clear understanding of the BCI-illiteracy mechanism or a solution to this problem has not been reported to date. In this study, we sought to demonstrate the neurophysiological differences between two groups (literate, illiterate) with a total of 52 subjects. We investigated recordings under non-task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
172
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(187 citation statements)
references
References 44 publications
12
172
1
2
Order By: Relevance
“…Most of these studies focus on inter-subject variability from a physiological [2][3][4][5][6], anatomical [7,8], or psychological [9,10] perspectives. Although precise distinction between user-related and system-related causes of performance variations may not be simple [11], these studies provide a better understanding of these causes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies focus on inter-subject variability from a physiological [2][3][4][5][6], anatomical [7,8], or psychological [9,10] perspectives. Although precise distinction between user-related and system-related causes of performance variations may not be simple [11], these studies provide a better understanding of these causes.…”
Section: Introductionmentioning
confidence: 99%
“…Three major MI studies on 193 subjects [26], 80 subjects [30] and 52 subjects [31], have specifically investigated this problem. These studies reported that between ~40% and ~60% of the subjects investigated could achieve an average accuracy in BCI control of only ~50% in the classic two-class scenario [32].…”
mentioning
confidence: 99%
“…Furthermore, it has been hypothesized that gamma oscillations directly affect the sensorimotor rhythm and are responsible for performance variations in BCI ; this insight may be potentially used to help BCI-illiterate subjects to learn how to control a BCI system. Other recent work has studied the impact of the delta and theta rhythms on BCI performance (Vuckovic and Sepulveda, 2008b;Ahn et al, 2013).…”
Section: Neurophysiological Backgroundmentioning
confidence: 99%